Pengaruh Kepribadian dan Konflik Kerja terhadap Kinerja Pegawai Negeri Sipil (PNS) pada Kantor Satuan Polisi Pamong Praja (SATPOL PP) di Kota Solok - Rahmadona Rahmadona; Afni Yeni; Esi Sriyenti (Jurnal bintang manajemen, 2025)
This research was conducted at the Civil Service Police Unit Office (Satpol PP) in Solok City. The purpose of this research was to find out the effect of personality and work conflict simultaneously on the performance of the Civil Service Police Unit Office staff in Solok City. In this study, the population in this study were all civil servants at the Civil Service Police Unit Office, Solok City, namely 39 people. By using a total sampling of 39 employees of the civil service at the Civil Service Police Unit Office, Solok City. Data collection techniques using a questionnaire / questionnaire. Based on multiple linear regression analysis of the variables Personality and Work Conflict Influence Employee Performance Y = -3.478 + 0.765X1 + 0.308X2+ e. From the t test conducted, it was found that the variable X1 Personality had an effect on employee performance with a known variable value tcount 5.557 > ttable 1.688 and sig 0.000 <0.05. Variable X2 Work Conflict on Employee Performance with a tcount of 1.975> ttable of 1.688 and sig 0.002 <0.05. From the F test conducted, it was found that personality and work conflict simultaneously influence employee performance. The F count is 58.836 > 3.259 and a significance value (0.000 < 0.05).